1998
DOI: 10.1016/s0008-6363(98)00107-2
|View full text |Cite
|
Sign up to set email alerts
|

Physio-pharmacological evaluation of myocardial performance: an integrative approach

Abstract: sion have altered out of all recognition compared to the Despite major advances in the understanding of carapproaches of 40-50 years ago. diovascular physiology and pathophysiology and the deWithin this context, the questions that are considered in velopment of new therapies in the 20th century, carthis article are: How should myocardial performance best diovascular disease is projected to become the leading be assessed? What are the advantages and disadvantages of overall cause of mortality worldwide within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
0
1
0
2
Order By: Relevance
“…The isolated papillary muscle provides a precise model to assess the mechanical properties of muscle where it is possible to accurately measure (and control) force and length in a multicellular preparation with relatively simple geometry. 29 We observed that LAAs induce a negative lusitropic effect in isotonic and isometric conditions ( Figure 3). Because isotonic relaxation strongly depends on calcium reuptake by the SR, 23 this result suggests an inhibitory effect of LAAs on SR function.…”
Section: Discussionmentioning
confidence: 70%
“…The isolated papillary muscle provides a precise model to assess the mechanical properties of muscle where it is possible to accurately measure (and control) force and length in a multicellular preparation with relatively simple geometry. 29 We observed that LAAs induce a negative lusitropic effect in isotonic and isometric conditions ( Figure 3). Because isotonic relaxation strongly depends on calcium reuptake by the SR, 23 this result suggests an inhibitory effect of LAAs on SR function.…”
Section: Discussionmentioning
confidence: 70%
“…In diesem Zusammenhang soll auch erwähnt werden, dass es durch den intraventrikulären Ballon zu einer Störung des endokardialen Endothels und hierüber zu einer Verschlechterung der globalen Ventrikelfunktion kommen kann. Dieser Effekt scheint jedoch nicht besonders ausgeprägt zu sein [26]. Letztlich könnte auch die im Folgenden angesprochene Ödembildung über eine Erhöhung der internen Arbeit zu dem verminderten Wirkungsgrad beitragen.…”
Section: Externer Wirkungsgradunclassified
“…Gegenüber anderen isolierten Präparatio-nen ließen sich zusätzlich die Interaktionen zwischen koronarvaskulären und ventrikulären Eigenschaften untersuchen. Letztlich kann bei diesem isolierten Modell auch der Einfluss des Endothels auf die myokardiale Funktion untersucht werden, da sich hier die Endothelzellen unter In-situ-Bedingungen physiologischen Stimuli unterwerfen lassen [26].Dieses experimentelle Modell hat in mehrfach modifizierter Form seinen festen Platz in der medizinischen Forschung gefunden. Daher sind Eigenschaften einzelner Varianten gut bekannt.…”
unclassified